2018
DOI: 10.1186/s12891-018-2085-8
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response relationship between cumulative physical workload and osteoarthritis of the hip – a meta-analysis applying an external reference population for exposure assignment

Abstract: BackgroundThere is consistent evidence from observational studies of an association between occupational lifting and carrying of heavy loads and the diagnosis of hip osteoarthritis. However, due to the heterogeneity of exposure estimates considered in single studies, a dose-response relationship between cumulative physical workload and hip osteoarthritis could not be determined so far.MethodsThis study aimed to analyze the dose-response relationship between cumulative physical workload and hip osteoarthritis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 25 publications
2
27
0
4
Order By: Relevance
“…These findings are similar to a previous register-based study of hip and knee OA, which showed that while men and women both had increased cumulative risk dependent on occupation, men had overall higher incidence of OA related to occupation 11. A meta-analysis of hip OA reported a similar dose–response relationship in men, but not in women, between cumulative lifting of heavy loads and the development of OA 12. Based on these studies in weightbearing joints, as well as previous biomechanical studies showing that strong grasp activities confer the highest loads to the CMC1 joint,2 it can be postulated that occupational joint loading has a deleterious impact on articular cartilage leading to OA.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are similar to a previous register-based study of hip and knee OA, which showed that while men and women both had increased cumulative risk dependent on occupation, men had overall higher incidence of OA related to occupation 11. A meta-analysis of hip OA reported a similar dose–response relationship in men, but not in women, between cumulative lifting of heavy loads and the development of OA 12. Based on these studies in weightbearing joints, as well as previous biomechanical studies showing that strong grasp activities confer the highest loads to the CMC1 joint,2 it can be postulated that occupational joint loading has a deleterious impact on articular cartilage leading to OA.…”
Section: Discussionsupporting
confidence: 89%
“…Кроме плечевых, локтевых и коленных суставов к настоящему времени появилось достаточно данных по ассоциации профессиональных факторов с ОА тазобедренного сустава. Профессиональные факторы риска развития ОА тазобедренного сустава изучены в 7 систематических обзорах [13,[19][20][21][22][23][24]. В обзоре A. Bergmann и соавт.…”
Section: ïðîôåññèîíàëüíûé îàunclassified
“…, который включал 51 исследование (526 343 человека), установлено, что такие профессиональные факторы, как подъем тяжестей, приседание на корточках и восхождение по лестнице, могут увеличивать риск развития остеоартроза Ряд авторов указывают[16][17][18][19][20][21] на ассоциацию частых приседаний с развитием ОА коленного сустава. Установлено, что при приседании нагрузка на коленный сустав в 2,5 раза больше, чем при ходьбе…”
unclassified
“…For prevention, a prerequisite is knowing whether work-related risk factors actually do matter in the onset or worsening of a disease [ 9 ]. In addition, if data allow, clinically relevant exposure threshold limits can be formulated, as is done for several other prevalent diseases like carpal tunnel syndrome [ 10 ], lateral epicondylitis [ 11 ], specific shoulder disorders [ 12 ], hip and knee osteoarthritis [ 13 , 14 ], and lumbosacral radiculopathy syndrome [ 15 ]. Regarding medical causation, many countries provide financial compensation when a disease is recognised as an occupational disease, like the Unites States of America, Canada and many countries in the European Union, like Italy, France, and Germany.…”
Section: Introductionmentioning
confidence: 99%